Violence and traumatic stress among Cambodian survivors and perpetrators of the Khmer Rouge genocide - Leakhena Nou (SSM - Mental Health)
This article presents the findings of a groundbreaking focus group cohort method of studying the residual impacts of traumatic stress and violence as reported by survivors and perpetrators of the Khmer Rouge genocide in Cambodia (1975–79). Both cohorts, separately participated in fifteen intensive focus groups lasting between one and five days across nine Cambodian provinces during 2012–13. This research focuses on the experiences of stress and violence by survivors and perpetrators during the genocide and since. The results of this study show that all 61 survivors and 58 perpetrators experienced multiple traumatic violent events during the genocide, and all lived in daily fear of being killed by the leaders of the Khmer Rouge. The results also show similar evidence of continued stress in both cohorts today, and parallel preoccupations with thoughts or memories of trauma and violence under the Khmer Rouge.